Building state capacity in Africa : new approaches, emerging lessons - Levy, Brian, 1954-; Kpundeh, Sahr John (WBI development studies., 2004)
"Building State Capacity in Africa draws on the experiences of public sector reform implementation in more than a dozen African countries to address such topics as the relationship between governance and economic development, public expenditure and accountability, anticorruption reform, decentralization, political structures, and the delivery of public services."--Jacket